MEDIA PEMBELAJARAN GLOBE DAN PETA PADA MATERI KENAMPAKAN ALAM (IPS) PADA SISWA KELAS IV MI MA’ARIF NU BATUANTEN - Hikmah, Nur; Ningsih, Tutuk (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to develop globe and map-based learning media for natural appearance (IPS) material for fourth grade students at MI Ma'arif NU Batuanten. This learning media is designed using an engagement-based approach and integration of the latest technologies such as augmented reality (AR) or virtual reality (VR) to enhance student learning experiences. This research uses descriptive qualitative method. This research was conducted using observation, interview, and documentation techniques. The evaluation results showed that globe and map-based learning media were effective in increasing students' understanding of natural features and motivating them to learn more actively. The participation of teachers and students in the evaluation process also shows an awareness of the importance of evaluation in the learning process. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. In conclusion, this study shows the benefits of using globe and map-based learning media in learning natural appearance. The results of this study provide a broader understanding of the development of innovative and effective learning media for social studies material for fourth grade students. The implication of this research is the importance of using creative learning media and integration with other learning methods to create a holistic and integrated learning experience.other teaching methods to create a holistic and integrated learning experience.